1983
DOI: 10.1128/iai.42.1.88-98.1983
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Pseudomonas aeruginosa outer membrane antigens examined by crossed immunoelectrophoresis

Abstract: By crossed immunoelectrophoresis 36 different anode-migrating antigens were demonstrated in sonicated antigen preparations of Psetidomonas aeruiginosa. We numbered these antigens to establish a reference precipitin pattern. Antigen no. 31 was identified as the lipopolysaccharide (LPS) antigen, because it was found to be responsible for the 0-group specificity and because it reacted with anti-LPS monoclonal antibodies and with Limlllus amoebocyte lysate. Purified outer membrane proteins F (porin), H,, and I use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…MATERIALS AND METHODS Bacterial strains and growth conditions. P. aeruginosa PAO1 strain H103 of 0 serotype 5 (IATS) (17,26) and a complete set of IATS serotype-specific strains were used for the isolation of LPS and outer membrane and for Formalin fixation of the whole-cell immunogen. The complete set of IATS serotype strains used was type 01 (ATCC 33348), type 02 (ATCC 33349), type 03 (ATCC 33350), type 04 (ATCC 33351), type 05 (ATCC 33352), type 06 (ATCC 33354), type 07 (ATCC 33353), type 08 (ATCC 33355), type 09 (ATCC 33356), type 010 (ATCC 33357), type 011 (ATCC 33358), type 012 (ATCC 33359), type 013 (ATCC 33360), type 014 (ATCC 33361), type 015 (ATCC 33362), type 016 (ATCC 33363), and type 017 (ATCC 33364).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MATERIALS AND METHODS Bacterial strains and growth conditions. P. aeruginosa PAO1 strain H103 of 0 serotype 5 (IATS) (17,26) and a complete set of IATS serotype-specific strains were used for the isolation of LPS and outer membrane and for Formalin fixation of the whole-cell immunogen. The complete set of IATS serotype strains used was type 01 (ATCC 33348), type 02 (ATCC 33349), type 03 (ATCC 33350), type 04 (ATCC 33351), type 05 (ATCC 33352), type 06 (ATCC 33354), type 07 (ATCC 33353), type 08 (ATCC 33355), type 09 (ATCC 33356), type 010 (ATCC 33357), type 011 (ATCC 33358), type 012 (ATCC 33359), type 013 (ATCC 33360), type 014 (ATCC 33361), type 015 (ATCC 33362), type 016 (ATCC 33363), and type 017 (ATCC 33364).…”
mentioning
confidence: 99%
“…Fresh colonies were picked from overnight cultures on PP2 agar plates for agglutination tests. For antigen preparation, colonies were grown in PP2 broth until the ODwo was approximately 0.5 to 0.8 (26).…”
mentioning
confidence: 99%
“…Another peculiar property of alginate is that excessive amounts in the experimental animals induces production of non-protective and low opsonizing antibodies (45). Using serum from a patient undergoing an exacerbation, it was demonstrated by cross immunoelectrophoresis that the serum recognized more than 30 distinct P. aeruginosa antigens (118). In contrast, serum from a patient in remission, who had been infected for 16 years, only recognized five antigens (119).…”
Section: Persistent Infection Phenotypes and Immunitymentioning
confidence: 99%
“…The seminal work performed to establish the basic concept for P. aeruginosa biofilms was done in the early 1980s. Using direct electron microscopic analysis of post-mortem lung tissues from CF patients, Lam et al (118) demonstrated that P. aeruginosa in CF lungs form aggregates or microcolonies (figure 4). Excessive amounts of alginate surrounding microcolonies during the course of chronic infections in CF directly impair antigen presentation.…”
Section: Persistent Infection Phenotypes and Immunitymentioning
confidence: 99%
“…as a control. All immunoelectrophoresis techniques were performed according to published procedures (Lam et al, 1983) with slight modifications. Circulating immune complexes were studied in the serum using a CIC Raji cell radioimmune assay (Dasgupta et al, 1987).…”
Section: Immunological Studiesmentioning
confidence: 99%